(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article clearly outlines the improvement of the effectiveness of suicidal prevention in public schools, the deterioration of the moral and ethical status of that unit and, ultimately, the negative impact on combat and preparation.